Science Teacher Noticing via Video Annotation: Links between Complexity and Knowledge-Based Reasoning. Issue 7 (3rd October 2022) - Zummo, Lynne; Hauser, Mary; Carlson, Janet
ABSTRACT: This study adds to the construct of science teacher noticing through an analysis that integrates concepts from pedagogical content knowledge (PCK) frameworks. It examines 929 instances of science teacher noticing made via video annotation tools (VATs) over the course of 38 early-career, secondary science teachers' participation in a two-year professional learning experience. This study asked specifically about: 1) interacting elements of a classroom (students, practice, content) teachers noticed in videos of their own practice, 2) patterns in knowledge-based reasoning evidenced in noticing, and 3) the role of content knowledge in such knowledge-based reasoning. Using mixed methods analysis, we found that the majority of annotations exhibited a singular focus (i.e. students, teacher practice, or content) and tended to focus on students and/or practice, with less attention to content. However, we also identified a statistically significant relationship between complexity of noticing (i.e. attention to multiple foci) and the presence of knowledge-based reasoning. Further qualitative analysis of the subset of annotations that attended to content suggested that such attention to content could be an important link within teacher noticing to connect practice to student thinking. This study highlights the value of scaffolding attention to content and to multiple foci within science teacher noticing. It also demonstrates the potential for VATs to facilitate noticing.